Innovative Approaches to the Teaching of Engineering Programmes in Nigerian Tertiary Institutions for Sustainable Economic Development - Haruna, Rabiu; A. Sara, Habibu; Rano , Habibu G. (MultiTech Publisher, 2024)
The Nigerian Tertiary education system has contributed to the development of the Nigerian economy for many years. With the current focus on sustainable economic recovery, it is important to ensure that the tertiary engineering programmes are being taught` in a manner that is both robust and innovative so as to facilitate the creation of graduates that are work ready. Therefore, this paper seeks to review the traditional approaches to teaching engineering programmes in Nigerian tertiary institutions and explore the need for innovation. In specific the paper provides an overview of engineering education in Nigeria, describes various stage of teaching/learning resources for engineering programmes, traditional approaches to the teaching of engineering programmes in Nigerian tertiary institutions, innovative approaches used in the teaching of engineering programmes, and at the end, the paper draw a conclusion towards the need for tertiary institutions to embrace the modern innovative approaches to the teaching of engineering programmes for the fact that, the knowledge and skills that will be developed in the individual learners will bring about sustainable economic development.